AIDS and American apocalypticism : the cultural semiotics of an epidemic - Long, Thomas L. (SUNY series in the sociology of culture., 2005)
"Using the analytical tools of literary analysis, cultural studies, performance theory, and social semiotics, AIDS and American Apocalypticism examines many kinds of discourse, including fiction, drama, performance art, demonstration graphics and brochures, biomedical publications, and journalism and shows that, while initially useful, the effects of apocalyptic rhetoric in the long term are dangerous. Among the important figures in AIDS activism and the arts discussed are David Drake, Tim Miller, Sarah Schulman, and Tony Kushner, as well as the organizations ACT UP and Lesbian Avengers."--Jacket